Effectiveness of a comic book intervention on mental health literacy among adolescents and youth in Burkina Faso: a randomized controlled trial protocol - Brandt, Irene; Some, Sylvain; Millogo, Ourohiré; Sourabié, Oumar; Burns, Jacob; Shinde, Sachin; Haucke, Matthias; Sivewright, Nathan; Neumann, Christine; Bajaria, Shraddha; Napon, Katian; Dah, Clarisse; et al. (BMC public health, 2025)
In Burkina Faso, nearly half of the population is under 15 years old, and one in four adolescents experience depression. This underscores the critical need to enhance mental health literacy among adolescents and youth, empowering them to manage their mental well-being effectively. Comic books offer an engaging approach to health education, yet their effectiveness in addressing mental health remains largely untested. Our study aims to fill this gap by evaluating the effectiveness of comic books in enhancing mental health literacy among adolescents and young adults aged 10-24 years.
Gesehen am 20.06.2025